Online Celebrity Endorsement and Brand Image on Customer Purchase Intention with the Mediating Role of Customer Ideal Self - Khosasih, Ricky Antonius; Sembel, Jacquelinda Sandra (Universitas Pelita Harapan, 2023)
The tight competition in sports shoes industry in Indonesia requires players in this market to be creative in promoting their products to win customers. One strategy is promoting their brand by adopting online celebrating endorsement. However, this strategy needs to be implemented carefully to match customer ideal self. This study aims to investigate the influence of online celebrity endorsement, brand image on purchase intention with the mediating role of customer idea self. A survey using online questionnaire was conducted among 180 private university students in Tangerang, Indonesia, Data was analyzed using Structural Equation Modeling Partial Least Square. The study reveals significant influence of celebrity endorsement, brand image and ideal self on purchase intention with a mediating role of customer ideal self.